Fabrication and studying the dielectric properties of (polystyrene-copper oxide) nanocomposites for piezoelectric application - Dalal Hassan; Ahmed Hashim Ah-yasari (Institute of Advanced Engineering and Science, 2019)
The preparation of (polystyrene-copper oxide) nanocomposites have been investigated for piezoelectric application. The copper oxide nanoparticles were added to polystyrene by different concentrations are (0, 4, 8 and 12) wt.%. The structural and A.C electrical properties of (PS-CuO) nanocomposites were studied. The results showed that the dielectric constant and dielectric loss of (PS-CuO) nanocomposites decrease with increase in frequency. The A.C electrical conductivity increases with increase in frequency. The dielectric constant, dielectric loss and A.C electrical conductivity of polystyrene increase with increase in copper oxide nanoparticles concentrations. The results of piezoelectric application showed that the electrical resistance of (PS-CuO) nanocomposites decreases with increase in pressure.